PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF , LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP KOMITMEN ORGANISASI - Wahid Hermawan (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to find the significance of the influence of participatory leadership, physical work environment and non-physical work environment on organizational progress. This type of research is a quantitative research method using SPSS 24. While the data collection technique in this study uses a media questionnaire with the Likert method. The population in this study were employees of STPMD/APMD Yogyakarta. The sampling technique used a saturated sample and a sample of 65 employees of STPMD/APMD Yogyakarta was obtained. Based on the tests that have been completed in this study, the results show that: (1) Participatory leadership style has no significant effect on organizational commitment. (2) The physical work environment has a significant effect on organizational commitment. (3) the non-physical work environment has a significant effect on organizational commitment. (4) participative leadership style, physical work environment, non-physical work environment simultaneously affect organizational commitment. Based on the results of the research conducted, it can be concluded that participatory leadership style has no significant effect on organizational commitment, physical work environment has a significant effect on organizational commitment, non-physical work environment has a significant effect on organizational commitment, and participative leadership style, physical and non-physical work environment simultaneously positive effect on organizational commitment.